Validity and Reliability of the Fundamental Motor Skills in Sports (FUS) Test for Iranian Children and Adolescents - Mohammad Hossein Zamani; Ayoub Hashemi; Elahe Siavashi; Razieh Khanmohamadi; Hamideh Saeidi (Shiraz University of Medical Sciences, 2024)
Background: Confident and proficient participation in physical activities throughout life relies on mastering Fundamental Motor Skills. Given the need for more effective solutions in assessing fundamental basic skills in both children and adolescents, the present study aimed to evaluate the validity and reliability of the Fundamental Motor Skills test in sports (FUS) among Iranian children and adolescents.Methods: This was a descriptive-correlation study with a cross-sectional design. A total number of 1500 children (750 girls and 750 boys) aged 7 to 14 with an average age of 10.63±2.54 were selected from eleven districts of Shiraz, Iran in the academic year of 2023-2024 through cluster sampling technique. For data collection, FUS test was used. The test was translated into Persian using an independent double-reverse translation method prior to its use. The content validity of the translated test was carefully verified and confirmed. Before testing each skill, the students were provided with a brief explanation about the importance and how to implement the skill. To analyze the data, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), Pearson intraclass correlation coefficient, and One-sample t-test were employed. A significance level of α=0.05 was applied and the data were analyzed using SPSS version 23.Results: The results of the confirmatory factor analysis indicated that all fit indices, except for Comparative Fit Index (GFI), exceed the threshold of 0.90. The results of the impact score revealed that all subscales achieved a score of 1.5 or higher, indicating satisfactory face validity. The results of the Content Validity Ratio (CVR) demonstrated that all subscales of the FUS test met or exceeded the threshold specified by the Lawshe Table (0.62). The results of the Content Validity Index (CVI) similarly revealed that all subscales of the FUS test attained a CVI score exceeding 0.79. Both inter-rater (0.96-0.97) and intra-rater (exceeding 0.96) reliability demonstrated considerable to nearly complete agreement. Detective agreements for FUS assignments ranged from 79.6% to 94.5%. A moderate positive correlation was noted between the Ball bouncing task and both the Forward roll (r=0.35; P=0.004) and Throwing & Catching tasks (r=0.39; P=0.002). Other relationships were either below average. Intraclass correlation coefficient (ICC) values, ranging between 0.93 and 0.98, affirm outstanding test-retest reliability.Conclusions: The results of our study demonstrated that the FUS test is both feasible and effective for use in school settings. Therefore, the FUS test holds promise in facilitating the enhancement of motor proficiency by offering a standardized and systematic means of evaluating Fundamental Motor Skills in school-age children and adults.